Body condition and its relationship with milk yield, reproduction and metabolic profile in dairy cows of the Bolivian tropics - Carizi Cherobin, Vanessa (2019)
The aim of this study was to analyze the relationship of the body condition score (BCS) with milk yield, reproductive efficiency and the postpartum metabolic profile in Holstein cows of the Bolivian tropics. Sixteen primiparous and multiparous Holstein cows aged between three and seven years were monitored during the first 150 days of lactation. The pre-partum BCS was better than during the post-partum period (p<0.05). However, there were no significant differences between BCS and daily milk yield, milk production in the first 150 days, body weight, calving to first service interval and calving to conception interval. The components of the metabolic profile (glucose, aspartate aminotransferase, alanine transaminase, total protein, albumin and urea) did not show significant differences due to BCS.